Association between Variations in Cell Cycle Genes and Idiopathic Pulmonary Fibrosis - Korthagen, Nicoline M.; van Moorsel, Coline H. M.; Barlo, Nicole P.; Kazemier, Karin M.; Ruven, Henk J. T.; Grutters, Jan C. (PLOS ONE, 2012)
Idiopathic pulmonary fibrosis (IPF) is a devastating and progressive lung disease. Its aetiology is thought to involve damage to the epithelium and abnormal repair. Alveolar epithelial cells near areas of remodelling show an increased expression of proapoptotic molecules. Therefore, we investigated the role of genes involved in cell cycle control in IPF. Genotypes for five single nucleotide polymorphisms (SNPs) in the tumour protein 53 (TP53) gene and four SNPs in cyclin-dependent kinase inhibitor 1A (CDKN1A), the gene encoding p21, were determined in 77 IPF patients and 353 controls. In peripheral blood mononuclear cells (PBMC) from 16 healthy controls mRNA expression of TP53 and CDKN1A was determined. Rs12951053 and rs12602273, in TP53, were significantly associated with survival in IPF patients. Carriers of a minor allele had a 4-year survival of 22% versus 57% in the non-carrier group (p = 0.006). Rs2395655 and rs733590, in CDKN1A, were associated with an increased risk of developing IPF. In addition, the rs2395655 G allele correlated with progression of the disease as it increased the risk of a rapid decline in lung function. Functional experiments showed that rs733590 correlated significantly with CDKN1A mRNA expression levels in healthy controls. This is the first study to show that genetic variations in the cell cycle genes encoding p53 and p21 are associated with IPF disease development and progression. These findings support the idea that cell cycle control plays a role in the pathology of IPF. Variations in TP53 and CDKN1A can impair the response to cell damage and increase the loss of alveolar epithelial cells.